FRI0414 Assessment of Salivary Gland Functions and Submandibular Gland Ultrasonography Findings During 10-Years Follow-Up in Patients with Sjögren's Syndrome. (9th June 2015) - Hashimoto, N.; Uchiyama, S.; Kitano, M.; Sano, H.; Iwasaki, T.; Hashimoto, T.
Abstract : Background: Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disease characterized by lymphocyte infiltration in salivary and lacrimal glands. Recently, salivary gland ultrasonography proved valuable for assessing salivary gland involvement in SS and seemed to exhibit good diagnostic properties. We previously reported that submandibular gland ultrasonography (SGUS) is a useful noninvasive and inexpensive procedure for the evaluation of the morphological changes of salivary gland involvement in SS patients (International Symposium on SS 2002, EULAR 2009, EULAR 2012). Objectives: The aim of this study was to examine association between salivary gland functions and SGUS findings during long-term follow-up in patients with SS. Methods: Fifty-six patients (56 females, mean age 68.0±9.9 years) with SS who fulfilled the Japanese criteria for SS were studied during long-term follow-up from 2003 to 2014. All US scans were performed by a single examiner who was blinded to the clinical data and used an US with a 7.5-MHz liner array transducer. US staging scores were assessed by glandular size, inhomogeneity and contrast of diagastric muscle (0: normal, 1: mild, 2: moderate, 3: severe structural damage). PD grading scores were graded by pulsed wave pattern in power Doppler US at the internal SG facial arteries (0: normal, 1: intermittent wave pattern, 2: disappearance of wave pattern). Results: The mean durations of follow up period were 10.0±1.2 years. The positive correlation between US staging scores and PD grading scores was found in all SS patients at the initial evaluation (r=0.853, p<0.0001). US staging scores and PD grading scores were also inversely correlated with glandular sizes (r=−0.861, p<0.0001; r=−0.800, p<0.0001) and the whole salivary flow by chewing gum test (r=−0.708, p<0.0001; r=−0.712, p<0.0001) in all SS patients at the initial evaluation, respectively. During follow-up, the whole salivary flow was decreased in all SS patients (9.3±6.8 vs 8.3±6.0 mL/10min., p<0.01). SG sizes were decreased in anti-SS-A antibodies (SS-A) negative but not in SS-A positive SS patients (−38.7±71.0 vs 12.5±54.8 mm 2, p<0.01). Both SG sizes and PD grading scores were significantly decreased in anti-centromere antibodies (ACA) positive than in ACA negative SS patients (SG sizes: −25.9±75.3 vs 15.7±48.6 mm 2, p=0.016; PD grading scores: 0.21±0.54 vs −0.22±0.59, p=0.010). Logistic-regression analysis demonstrated close association between decreased whole salivary flow during follow-up and factors such as age (<60 years old, OR=3.91, 95% CI: 1.10-13.90), SG sizes (200mm 2, OR=4.82, 95% CI: 1.25-18.54) and positive ACA (OR =4.38, 95% CI: 1.04-18.46) at the initial evaluation. Conclusions: The present study demonstrated that whole salivary flow was decreased in early stage of SS patients (<60 years old, SG size200mm 2 ) during 10-years follow-up. In addition, positive ACA was associated with decreased whole salivary flow, SG size and blood flow during follow-up. SGUS may be a useful tool for the examination of disease progression in ACA-positive early stage SS patients. Disclosure of Interest: None declared